Conceptualizing Domestic Violence Within Clinical Documentation - María Atiénzar-Prieto; Shannon Dhollande; Silke Meyer; Diksha Sapkota; Karen-Ann Clarke (SAGE Publishing, 2024)
Domestic and family violence (DFV) is a global issue with significant impacts on victim-survivors. The emergency department (ED) serves as the initial point of contact for victim-survivors. Given the significant role that clinical notes play in the management of patients and the communication between healthcare professionals, understanding how healthcare practitioners describe and document abuse reported in emergency settings is crucial. Yet, there remains a gap in understanding how health professional document DFV in the medical records of women presenting to the ED. Therefore, this qualitative descriptive study explored how DFV is documented in patient records of women presenting to the ED. Clinical notes from healthcare workers, including medical practitioners, nurses, social workers, mental health clinicians and ambulance officers, were qualitatively analyzed. Overall, the study included 43 presentations from 32 women (aged 18-56 years old) who visited a regional ED, during which instances of DFV were noted. An inductive content analysis resulted in the identification of four categories, including (a) DFV articulated in direct speech, (b) Unambiguous DFV, (c) Unconfirmed DFV, and (d) Problematic relationship. Although most references to DFV in the clinical notes included direct quotations from the patient's descriptions of abuse or were documented unambiguously by healthcare professionals, a notable number of clinical notes exhibited a degree of caution or reluctance to acknowledge DFV dynamics when describing these events. These findings support the need for sustained and consistent professional training among healthcare professionals concerning the identification, documentation, and response to disclosures, suspicions, and allegations of DFV to better support victim-survivors presenting to the ED and other hospital settings.